Meningkatkan kinerja Perusahaan Melalui Manajemen Risiko: Pendekatan dalam Manajemen Sumber Daya Manusia - rizka, Miftahul (Maliki Interdisciplinary Journal, 2024)
Risk management has become an important aspect of modern business strategy and aims to identify, assess and manage risks that can impact business performance. An important aspect of risk management is human resource management (HR), which handles risks related to human factors in an organization. This article discusses HR risk management approaches and how these approaches can improve organizational performance. This article focuses on HR risk identification, risk analysis, risk management strategy development, appropriate recruitment and selection, talent development, performance management, conflict management, effective communication , evaluation and adaptation, as well as helping organizations manage their HR Provides practical guidance to strengthen your fundamentals.By adopting this approach, companies can reduce HR-related risks and effectively improve business performance in a dynamic business environment.